Does a History of IUD Contraceptive Usage Affect Placental Location in Future Pregnancies? [9P]. (May 2018) - Bergh, Eric P.; Duncan, Sarah; Pan, Stephanie; Overbey, Jessica; Stone, Joanne; Ferrara, Lauren
Abstract : INTRODUCTION: It is unknown how a history of prior IUD usage affects future pregnancy implantation outcomes. Our objective is to determine the impact of prior IUD usage on placentation and obstetric outcomes in subsequent pregnancies. METHODS: Retrospective matched cohort study, where one group of patients had placement of an IUD at Mount Sinai in the last 7 years (2010-2016) prior to a pregnancy and one group with no history of IUD usage. Patients are matched 2:1, two no IUD placements for each IUD patient. They are matched by parity, unit in which they received care, and delivery time (±3 days). Outcomes were obtained via chart review. RESULTS: 1736 patients underwent IUD placement during the study period, of which 71 subsequently had their device removed, became pregnant and delivered. Four patients were removed from the analysis: 2 delivered at outside institutions, a patient with a 14 week loss and a patient with a twin pregnancy. In all, 67 patients had a subsequent singleton pregnancy outcome beyond 20 weeks. There were no significant differences in placental location nor in the incidence of low lying placenta or placenta previa. Secondary outcomes of EBL, fetal weight, and mode of delivery did not differ. Finally among 43 patients for whom the duration of IUD usage was known, there was no evidence of an association between either duration of IUD usage nor duration of time from removal to delivery on placental outcomes. CONCLUSION: History of IUD usage does not appear to affect the location of placentation in future pregnancies.